DERMATOLOGICAL TOXICITY OF CANCER PATIENTS RECEIVING SMALL MOLECULE EPIDERMAL GROWTH FACTOR RECEPTOR INHIBITORS – A PROSPECTIVE OBSERVATIONAL STUDY - RG, ANAND; BABY, MINU; R, VISHNU; MATHEW, ANU ELINE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study are as follows: (1) To study the incidence of dermatological toxicity in patients receiving small molecule epidermal growth factor receptor inhibitors. (2) To assess the severity of dermatological toxicity. Methods: This prospective observational study of 66 cancer patients carried out in the Department of Radiotherapy, Government Medical College, Thiruvananthapuram. Patients with histopathological evidence of cancer receiving small molecule epidermal growth factor receptor inhibitors and satisfying inclusion criteria were taken up in the study after obtaining written informed consent. History and clinical examination before initiation of treatment done. Data regarding the occurrence of developing dermatological toxicities were obtained by questioning for symptoms and with the help of structured proforma. Severities of dermatological toxicities were assessed, and toxicity grading was done. Results: Sixty-six cancer patients enrolled in the study. The mean age of the patients was 62.4 years. The prevalence was higher in men (53%). Sixty-three patients (95.5%) developed at least one dermatological toxicity. The most common dermatological toxicity observed was papulopustular rash (68.2%), followed by xerosis (66.7%) and pruritus (59.1%). Conclusion: The present study has thus determined the incidence and severity of dermatological toxicity of cancer patients receiving small molecule epidermal growth factor receptor inhibitors.